If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6=k=-9
We move all terms to the left:
-6-(k)=0
We add all the numbers together, and all the variables
-1k-6=0
We move all terms containing k to the left, all other terms to the right
-k=6
k=6/-1
k=-6
| u=-10+6u | | M=4m+15m-7 | | -14=4(v-5)-2v | | 3x(x-1)=2x-3+3x | | 8+45=a-53 | | 3x^2-7x+16=0 | | 7-2c=-3c | | -x+10=4x-15 | | 3a+10=65 | | x2+9x=0 | | 20n+6=n-374 | | .9=x/36 | | -10g=9-7g | | 1/8-8/9w=1/9w+9/8 | | -4(2x-3)+3x-5=-18 | | (2x-9)=15 | | 9w-6=3w+7 | | .90=x/36 | | -5(x+1)-11=13+6 | | -8+2r-6r=-8r-4r | | a-344=-9a-4 | | 5(2x-1)-4x-1=-12 | | -17x=-208 | | 200m-100m+57,300=60,900-200m | | -5=2x-13 | | .75=x/36 | | 3/5y+11=-1/3y+8 | | -9(10k+1)=-10(9k-1) | | 6z=4(1/2z-8 | | q+239=-5q-7 | | 9c-4c=4 | | 75=x/36 |